Some congruences related to harmonic numbers and the terms of the second order sequences - Omur Nese; Koparal Sibel (Mathematica Moravica)
In this paper, with helps of some combinatorial identities, we investigate various basic congruences involving harmonic numbers and terms of the second order sequences Ukn and Vkn.